Al-Qur'an and Moderation of Religion: Middle Way to Harmony - Muhammad Ihsanul Wathony; Lalu Muhamad Rusdi Fahrizal (al-Afkar, Journal For Islamic Studies, 2024)
Basically, the principle of moderation (wasathiyah) has been known for a long time in the Islamic tradition—even this principle comes together with the vision of Islam itself. From several interpretations of the Al-Qur'an verses on the moderate principle (washatiyah) presented in this study, this research—directly and firmly refutes the notion that Islam is a religion that teaches violence. This research also shows how Islam is a religion that upholds human values. Through the three pillars; justice, balance and tolerance contained in the principle of moderation (wasathiyah)—the peace and harmony of life that mankind in various parts of the world yearns for can be realized.